Exploring the ethical tensions surrounding antimicrobial stewardship in UK companion animal veterinary practice - Cartelet, Clio (2021)
Antimicrobial resistance (AMR) is increasingly recognised as a critical problem in human and veterinary medicine. One of the key strategies to combat AMR is to promote responsible antimicrobial stewardship and ensure prescribers use an appropriate antimicrobial for a clinical condition, at a correct dose and frequency, and only if absolutely indicated. While multiple studies have focused on the ethical tensions surrounding antimicrobial stewardship in human medicine, equivalent work has seldom been carried out in the veterinary sector, particularly relating to companion animal medicine. In addition, limited empirical ethics work has been carried out which uses qualitative approaches. This work examines the ethical tensions surrounding antimicrobial prescription in companion animal practice through veterinarians’ experience of the ethical issues raised. The perspectives of twenty-five companion animal veterinarians in the UK were explored through in-depth qualitative interviews. A descriptive ethical approach was used to examine veterinarians’ characterisation of responsibility to the patients, the influence of the veterinarian-client relationship, the role of experience and evidence in clinical decision-making, and society’s perceived expectations of companion animal veterinarians. This empirical work identifies that, when applying antimicrobial stewardship principles, veterinarians are surrounded by complex and intertwined ethical tensions. Veterinarians experience a near set of tensions that result from dilemmas that emerge from the veterinarian-client-animal triad. Like any treatment decision in veterinary practice, antimicrobial prescription requires the veterinarian to promote and protect the health and welfare of their patients, while respecting the client’s beliefs, circumstances and means. A ‘far’ set of tensions, which to date have not been explored as widely, relate to societal pressures on, and expectations of, the veterinary profession in relation to AM prescribing. The duties of practicing evidence-based veterinary medicine alongside applying precautionary antimicrobial stewardship guidelines to protect human public health, create unique ethical dilemmas. These responsibilities compete with each other in a complex web that veterinarians described as a daily navigation. In particular, the tensions represented as near and far ethical challenges resonate with the concept of ‘moral distance,’ which relates to the human tendency to care for those who are close to us physically and emotionally above those further removed from our life and experiences. Antimicrobial stewardship requires weighing the interests of an immediate individual patient whose health and welfare are the foundations of the clinician’s work against the interests of a nebulous population that cannot be directly visualised or interacted with. Consequently, ‘moral distance,’ when considered alongside the aforementioned ethical tensions, is relevant to any discussion of antimicrobial stewardship. Antimicrobial stewardship needs to be better curated based on this understanding of veterinarians’ experience and ensure the promotion of effective antimicrobial stewardship in companion animal practice, with a clear message regarding the clinical or precautionary components of various guidelines, and while addressing the question of patients’ safety. Communication with veterinary professionals should also be improved by taking into account the nature and complexity of the ethical challenges they face when prescribing antimicrobials, including the impact stress and moral distress can have on the profession.